A Bio-Inspired Framework for Wireless Sensor Network Using Mobile Sensors - Ponnusamy , Vasaki; Azween, Abdullah (2010)
Energy-constrained sensors deplete their energy quickly due to routing sensor data to the base station and also sensing the event. Energy depletion at these nodes causes routing hole and reduces network lifetime. This paper introduces the method of exploiting mobile nodes in the sensor network to increase network lifetime and node lifetime. This mobile nodes, known as mobile agents act as routing agents to increase network lifetime as well as move in position searching for energy, recharge and deliver the harvested energy to static energy depleted nodes. The mobile agent proposed in this paper travels between the static sensor nodes and base station in order to collect sensed data from the sensor nodes and relay it to the base station. Moreover the mobile agent also performs energy harvesting to increase node lifetime. The proposed architecture is inspired by plant biology (botany) based mechanism of the symbiosis interaction between plant root system and microbes in the rhizosphere (soil)